ANALISIS PENDAPATAN PETANI PENANGKAR BENIH PADI (ORYZA SATIVA L.) DI KABUPATEN SIMALUNGUN - Dewi Sartika Laurencia Br. Manurung; Siti Mardiana; Mitra Mustika Lubis (Agroland: Jurnal Ilmu-ilmu Pertanian, 2020)
The existence of seed breeder farmers is one of the efforts to increase the availability of rice seeds which is very limited. Therefore, some rice seed breeder farmers start seed businesses either using their own capital for developing their private businesses or using facilities provided by the government. In Simalungun regency, the seed breeder farmers are divided into two groups i.e. fostered and independent seed breeders. Data was analyzed using a qualitative approach, income analysis, normality test, t test and F test. The normality test values showed that the value of Kolmogorov-Smirnov Z was 0.368>0.05 indicating that the data are normally distributed. The income between the two groups was significantly different based on the F test which F-value>F-table. Based on the t test, the income of the fostered seed breeder was lower than its counterpart. Keywords: Income Difference, Seed Breeder and Simalungun.